2017
DOI: 10.17222/mit.2015.256
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the composite structure and parameters after an exposure to a synergic action of various extreme conditions

Abstract: The research presented in this paper is aimed at studying the properties of composites designed for a redevelopment of reinforced concrete structures where it is possible to expect an increased risk of fire, i.e., shock actions of extreme temperatures. Such conditions may occur, for example, in transport constructions, particularly in tunnels. We have developed two recipes (formulas) for materials based on a polymer-cement matrix and a porous filler. These materials were subjected to cyclic freezing and de-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…[1] [15] In 2017 Melichar found that composite materials containing lightweight aggregates based on sintered fly ash are in terms of properties changes (strength characteristics and microstructure) during extreme temperature effect (up to 1000 °C) relatively stable in comparison with common mortars and concrete. [16] Among others, he investigated various cooling regimes (gradual and shock decrease of temperature). The considerably positive effect of lightweight aggregates based on sintered fly ash (in polymer-cement composites during extreme temperature exposure) was confirmed too.…”
Section: Introductionmentioning
confidence: 99%
“…[1] [15] In 2017 Melichar found that composite materials containing lightweight aggregates based on sintered fly ash are in terms of properties changes (strength characteristics and microstructure) during extreme temperature effect (up to 1000 °C) relatively stable in comparison with common mortars and concrete. [16] Among others, he investigated various cooling regimes (gradual and shock decrease of temperature). The considerably positive effect of lightweight aggregates based on sintered fly ash (in polymer-cement composites during extreme temperature exposure) was confirmed too.…”
Section: Introductionmentioning
confidence: 99%
“…CT was used to evaluate construction materials by Melichar et al [6,7] while assessing the damage of thermally overloaded polymer-cement composites. The method was also used by Lublóy et al [8] for the determination of pore distribution in asphalt concrete and by Balázs et al [9] while monitoring the distribution and orientation of diffused concrete reinforcement.…”
Section: Introductionmentioning
confidence: 99%